2012
DOI: 10.2174/187152712800792901
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Tyrosine Hydroxylase in Parkinson’s Disease

Abstract: Tyrosine hydroxylase (TH) is the rate-limiting enzyme in brain catecholamine biosynthesis, and tetrahydrobiopterin is its cofactor. Research has focused on identifying mechanisms of TH activity regulation. TH activity is modulated by the cofactor itself, and is enhanced by several kinases phosphorylating key serines in the TH regulatory domain. Aside from these, the mechanisms that control TH gene transcription and TH mRNA translation are also related with the regulation of TH activity. Parkinson's disease (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 0 publications
2
63
0
Order By: Relevance
“…Moreover, TH is the rate-limiting enzyme in the synthesis of catecholamine neurotransmitters such as dopamine. TH activity is progressively decreased following the loss of dopamine neurons in the substantia nigra in PD patients (Zhu et al, 2012). Our results showed that PLA reduced the loss of TH-positive neurons in substantia nigra of MPTP mice in vivo.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, TH is the rate-limiting enzyme in the synthesis of catecholamine neurotransmitters such as dopamine. TH activity is progressively decreased following the loss of dopamine neurons in the substantia nigra in PD patients (Zhu et al, 2012). Our results showed that PLA reduced the loss of TH-positive neurons in substantia nigra of MPTP mice in vivo.…”
Section: Discussionsupporting
confidence: 50%
“…However, the reliability of the latter finding is debatable given a small sample of 10 patients was investigated and to the best of our knowledge these results have not been replicated or followed up on thus far. One reason TYR may not actually benefit every, if any, case of Parkinson's may be that the disorder is associated with reduced expression of the TH enzyme (Zhu et al, 2012), which converts TYR into L-DOPA. Low TH activity would contribute to decreased DA synthesis.…”
Section: Clinical Populationsmentioning
confidence: 99%
“…TH, the rate limiting enzyme in dopamine synthesis in the brain, is the gold standard marker in the identification of dopaminergic neurons. 33 Ventral diencephalic TH populations are highly sensitive to MPTP exposure, and a decreased TH population leads to a pronounced reduction in the number of dopaminergic cells in the diencephalon. 34 Of note, MPP + alone cannot effectively induce neurodegeneration with animal models as it cannot cross the blood−brain barrier.…”
Section: Featured Lettermentioning
confidence: 99%